Morphological and Biomolecular of the Atergatis floridus Crab in the Intertidal Zone of the Minanga Coast, Manado City - Tamara Angela Gabriela Siahaan; Darus Saadah J. Paransa; James J.H. Paulus; Stenly Wullur; Remy E.P. Mangindaan; Pankie Pangemanan (Jurnal Ilmiah Sains, 2022)
This study examines the morphology and biomolecules of the Atergatis floridus crab found in the Intertidal Zone of the Minanga Beach, Manado City. Species identification was carried out by morphological and biomolecular analysis of DNA barcoding using the COI gene. Samples were collected in February and the isolation stage was in March 2022. The method used was the roaming method, namely exploring the research location to catch samples of crabs on the coast and catching crabs directly using hands protected with gloves and a flashlight for lighting. The morphological characters of concern are the shape of the carapace color and the anterior, posterior and abdominal characters. Furthermore, muscle tissue samples were taken from the crab claws for DNA isolation and sequencing processes at the company's first base laboratories, Malaysia. Based on the results of the research, samples that have been studied morphologically and sequenced show that 99.70% of the species are Atergatis floridus. Keywords: Atergatis floridus;  DNA barcode; Manado City; morphology Morfologi dan Biomolekuler Kepiting Atergatis floridus di Zona Intertidal Pesisir Pantai Minanga, Kota Manado  ABSTRAK Studi ini menelaah morfologi dan biomolekuler kepiting Atergatis floridus yang terdapat di Zona Intertidal Pesisir Pantai Minanga, Kota Manado. Identifikasi spesies dilakukan dengan pendekatan analasis morfologi dan biomolekuler DNA barcoding menggunakan Gen COI. Sampel dikoleksi pada bulan Februari dan tahapan isolasi pada bulan Maret 2022. Metode yang digunakan adalah metode jelajah, yakni menjelajahi lokasi penelitian untuk menangkap sampel kepiting di pesisir pantai dan penangkapan kepiting secara langsung menggunakan tangan yang dilindungi dengan sarung tangan dan senter untuk penerangan. Karakter morfologi yang menjadi perhatian adalah bentuk warna karapas dan karakter anterior, posterior dan abdomen. Selanjutnya diambil sampel jaringan otot pada bagian capit kepiting untuk dilakukan isolasi DNA dan proses sekuensing pada perusahaan first base laboratories, Malaysia. Berdasarkan hasil penelitian sampel yang telah ditelaah secara morfologi dan disekuens menunjukkan bahwa 99.70% spesies tersebut adalah Atergatis floridus. Kata kunci: Atergatis floridus; DNA barkoding; Kota Manado; morfologi